Determination of geriatric patients' drug profile and identify their pharmaceutical care requirements by determining potential risk factors - OKUYAN, BETÜL (SPRINGER, 2011)
Purpose: The aim of this study is to evaluate the geriatric drug usage, assess the appropriateness of their drug treatment and identify their pharmaceutical care requirements. Patients and methods: The demographic, clinical and drug data of the patients was obtained. Patients' knowledge about their drugs was also assessed. The patients at risk of drug induced problems were defined and a risk map was determined. Patients, who were 65-years-old and over and live in a nursing home in the Anatolian part of Istanbul, were included in our study. Results: Polypharmacy was identified in 44% of those included in the study (total of 146 patients who take drug therapy). Eighty of the patients (54.8%) did not know reason they were taking drugs. Eighty-eight of the patients (60.3%) were not aware how or when they should take drugs. Although, 24 patients (16.4%) were using their drugs by self-administration, the drugs of 122 patients (83.6%) were administered by their nurse; 24.65% of patients were in a high-risk category. The mean of number of drug used by patients was 5.89 +/- 3.61. Discussion and conclusions: According to our results, patients have lack of knowledge about drug usage and they have rarely been informed about rationale drug usage. First, it is necessary to determine geriatric patients' pharmaceutical care needs in order to prevent and solve their drug-related problems. Pharmacists will contribute to the development and spread of patient oriented pharmacy services by working in specialist geriatric teams with physicians, nurses and other health professionals. (c) 2011 Elsevier Masson SAS and European Union Geriatric Medicine Society. All rights reserved.
Keywords: Pharmaceutical care; Geriatric patient; Polypharmacy; Clinical pharmacy; INAPPROPRIATE MEDICATION USE; EXPLICIT CRITERIA; NURSING-HOMES